Evaluation of heat exchanger on thermoacoustic performance - Yahaya, Mohd Zubir (2013)
Thermoacoustic devices have the potential to provide electricity from waste heat to more efficiently use energy resources and to provide new access to electricity for millions of persons around the world. There are many factor influence thermoacoustic performance and this study was focused on a new design of thermoacoustic’s heat exchanger and evaluation of its performance in terms of thermal analysis. Through several ideas from researchers in this field, this study was produced with three designs of heat exchangers which are wiretype, fingertype and startype that specifically one of them will be used in experimental test later. Theoretical analysis shows that heat conduction through a full body of heat exchanger are 67.36 W and 39.81 W for both copper and aluminium. Analyzing heat conduction of a fin separately by types of heat exchangers, the highest value of heat conduction through a fin was recorded by startype heat exchanger’s fin using copper as material which is 32.84 W. By using ANSYS-CFX software, the heat exchanger’s designs were simulated with two thermal conditions which are steady state conduction and transient conduction by substituting material between copper and aluminium to see the engagement between theoretical analysis and numerical analysis. There are three inlet temperatures that are assumed will be supplied by constant waste heat which are 200°C, 350°C and 500°C. The simulation on both steady state and transient condition found the copper is better in thermal or heat conductor than aluminium due to high value of thermal conductivity, k. In terms of design, startype heat exchanger recorded the fastest time to distribute temperature compared to wiretype and fingertype heat exchanger. As a conclusion, the combination between startype design and copper material will produce the best heat exchanger that will be used in experimental test of thermoacoustic system.